Legal Transformation of Artificial Intelligence Technology to Strike a Balance Between Law and Technology - Alfiani, Francisca Romana Nanik; Santiago, Faisal (Rechtsnormen: Journal of Law, 2024)
Background: Artificial Intelligence (AI) is transforming various sectors globally, including business and healthcare. In Indonesia, this transformation is supported by initiatives like the Palapa Ring project and 5G infrastructure. However, the rapid growth of AI poses legal and ethical challenges. Current regulations, such as the Personal Data Protection Act, are insufficient to address the complexities of AI technology, creating a gap between legal frameworks and technological advancements. Objective: This study aims to identify the gaps in Indonesia’s AI-related legal frameworks and propose strategies for balancing the development of law and technology to ensure ethical and accountable AI integration. Methodology: Using a normative legal research approach, the study examines existing AI-related legal frameworks, compares international regulations, and analyzes their implications for Indonesia. Findings: The study reveals that while online motorcycle taxis contribute significantly to the transportation sector, current legislation does not fully recognize them as legitimate public transport providers. This gap affects passenger protection and the certainty of service standards. Conclusion: To ensure safety, reliability, and legal clarity, it is imperative to establish a comprehensive legal framework that formally categorizes online motorcycle taxis as recognized public transportation.